PEMBERDAYAAN PEREMPUAN MELALUI PENGOLAHAN BUAH NAGA MERAH MENJADI SELAI SEBAGAI PRODUK PENGEMBANGAN AGROWISATA REMBANGAN KABUPATEN JEMBER - Khoirul Hakimah Annisa; Pudjo Suharso (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2016)
The problems until now faced by Indonesian is poverty. The poverty rate large enough was felt society Kemuning Lor village resulting ini people are difficult to grow. Because empowerment is one of strategy selected to reduce poberty itself. This research aims to empower women in Kemuning Lor village, especially the dragon fruit plantation workers who still have limited skill and knowledge so that leading to low levels of income owned. This research uses Action Research approach. Data collection methods used in this research is the method of documentation, observation, interviews, questionnaires assessing the success of the training and the Focus Group Discussion (FGD). Data analysis was performed using Rapid Rural Appraisal (RRA). This method aims to make observations about the condition of women in Kemuning Lor village, and then used as a reference in making planning decisions implementation. Based on the research results, jam resulting from the red dragon fruit can be used as a development product of Rembangan agrotourism in Jember regency. Its making an easy process, as well as the tools and materials also easy to get could provide the opportunity for women in Kemuning Lor village to increase their income through selling of red dragon fruit jam. In addition, the benefit of the empowerment of women through processing of the red dragon fruit it is increasing skill and knowledge women in Kemuning Lor village in processing red dragon fruit be jam.